A Case of Lung Cancer with Brain Metastasis following Late-Onset Bipolar Disorder. (2nd April 2021) - Shen, Shin-Heng; Lee, Shwu-Hua
Abstract : Objective . To describe a case of lung cancer with brain metastasis in a patient who developed new late-onset bipolar disorder 2 years previously. Background . The typical onset age of bipolar disorder is approximately 20, and the first episode is usually a depressive episode. It is still not clear which age-specific factors contribute to the underlying risk. Materials and Methods . A 65-year-old male patient presented with a new-onset manic episode characterized by labile mood, impulsivity, decreased need for sleep, and grandiosity. He was diagnosed with late-onset bipolar disorder after excluding other possible physiological conditions. He was hospitalized in the acute psychiatric ward, and a combination of mood stabilizers and antipsychotics was prescribed. His mental condition improved, and he remained stable for 2 years. However, he experienced abrupt cognitive decline for 2 months and was referred to the emergency room for physiological examination. Results . The patient was diagnosed with lung cancer with brain metastasis by brain magnetic resonance imaging and whole-body positron emission tomography. Conclusion . In geriatric patients, who are at high risk of multiple medical conditions, excluding secondary causes of bipolar disorder is important.